The Transformation of the Function of Jeep Vehicles from Combat Vehicles to Urban Cultural Identity: An Ethnographic-Archaeological Study in the City of Bandung - Benyamin Lufpi (International Journal Labs, 2026)
Historic vehicles represent an important category of movable cultural heritage because they contain historical values, technological development, and collective memories of societies. However, the preservation of military vehicles in Indonesia remains limited, particularly regarding their transformation from functional war equipment into cultural identity symbols. This study aims to reconstruct the transformation process of military jeep vehicles, particularly Willys MB and Ford GPW, from instruments of warfare during the Indonesian independence period into cultural heritage objects within the urban community of Bandung. This research employed a qualitative ethnoarchaeological approach by combining material culture analysis and community ethnography. Data were collected through participatory observation, in-depth interviews with historical jeep communities, artifact documentation, and analysis using cultural biography theory, collective memory theory, and the Burra Charter framework. The results reveal three transformation phases: (1) 1945–1960, when jeeps functioned as combat and guerrilla mobility instruments; (2) 1960–1990, when they shifted into civilian utility vehicles; and (3) 1990–present, when preservation communities transformed them into symbols of historical memory and urban identity. The discussion shows that preservation practices, public commemorative activities, and community narratives play significant roles in maintaining the cultural meaning of these vehicles. This study concludes that historic jeeps are not merely technological artifacts but dynamic heritage objects that contribute to collective memory, national identity, and community-based heritage preservation in Indonesia.